Chironomidae (Diptera) from mountain lakes of the Eastern Carpathians, Romania: First records and insight into diversity - Peter Bitušík; Veronika Slobodníková; Milan Novikmec; Adam Dudáš; Ladislav Hamerlík (ZooKeys)
Lakes at high altitudes are extremely sensitive to environmental stressors at both local and global scales, making them important sentinels of the changing world. Chironomidae, the most diverse group of benthic macroinvertebrates inhabiting mountain lakes, respond to various environmental impacts, making them important bioindicators of the lake’s ecological status. This study aimed to provide the first insight into chironomid diversity in high-altitude lakes from two mountain ranges of the Romanian Eastern Carpathians: the Maramures, and the Rodna Mountains. Floating chironomid material was collected by skimming the water surface with a hand net from 16 lakes at elevations ranging from 1378 to 1922 m a.s.l. A total of 50 species/ taxa were collected, including nine new records for Romania. Notes on newly recorded species’ distribution, ecology and taxonomy are provided. In addition, an identification key for Procladius choreus and P. sagittalis based on thoracic horn characteristics is given. With our addition, the total number of chironomid species known from Romania is now 526. The study provides a baseline for future research on chironomid diversity, ecology, and biogeography in high-altitude lakes of the Carpathian Mountains.